Comparison of two anaesthetic drug (propofol and midazolam) versus (chloral hydrate) for pediatric sedation in MRI suite - Mojgan Rahim; Afzal Shamsi; Samer Ahmed Jawad Al Hashim; Asghar Hajipoor; Ali AbdulZahra Jasim (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background and aims: Magnetic resonance imaging (MRI) is a common diagnostic imaging procedure for children that typically takes 30 - 60 minutes to complete. As a result, during an MRI, pediatric patients' cooperation is crucial. Propofol is a sedative-hypnotic agent that is frequently used to stay calm children undergoing diagnostic or therapeutic procedures. Midazolam can be administered concurrently with propofol to reduce the amount of the drug that is required to achieve an adequate level of sedation. Chloral Hydrate: is a non-opiate, non-benzodiazepine sedative-hypnotic drug that has long been utilized for pediatric sedation at a dosage of 20 - 100 mg/kg, Chloral hydrate can increase the number of incidences of bradycardia, apnea and decreased oxygen saturation, Sedation lasts from one to two hours after administration, with the duration of its action being quite variable. This study aimed to compare which of these drugs is more stable for vital signs and which is more in-depth for sedation and less side effect on the Pediatric patients during MRI examination.Material &methods: in this cross-section 70 pediatric participants were enrolled in the propofol-midazolam and chloral hydrate group male and female age range (1-12 years old) who were candidate for elective exam and were in class I, II of ASA, parental consent, and NPO, participated in this study. Before, during and after examination we were assessed (SPO2, HR and MAR), Time to achieve sedation, Duration of MRI (min) and Duration of Recovery in both group (propofol-midazolam and chloral hydrate) we measure Side effect (long sedation, nausea and vomiting, agitation) and Respiratory Complication (Tachypnea, laryngeal spasm Respiratory Distress, Decrease SPO2).Result: the age in this study (1-12 years). our finding show highly significant statistical differences in anesthetic drug (propofol and midazolam) group versus chloral hydrate group in time to achievesedation, duration of MRI and duration of recovery for pediatric sedation in MRI suite at P < 0.001. At P < 0.05 there were significant statistical differences in anesthetic drug (propofol and midazolam) group versus chloral hydrate group in side effect for pediatric sedation in MRI suite. Finally, our analysis showed no apparent distinction between both groups in terms of age, weight, the type of MRI, parental satisfaction, or UN satisfaction of the radiologists.Conclusion: This study shows that using propofol-midazolam versus chloral hydrate to sedate pediatric for MRI examination takes less time and, as a result, allows for a more effective use of the MRI scanner's resources. The time between scans is particularly reduced by the extremely brief induction time. We feel that utilising propofol sedation allows for more effective use of the MRI facility and justifies the paediatric anesthesiology service's increasing involvement in this extremely expensive resource.